2020
DOI: 10.1021/acs.inorgchem.9b03621
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Mechanics/Molecular Mechanics Study of the Reaction Mechanism of Glyoxalase I

Abstract: Glyoxalase I (GlxI) is a member of the glyoxalase system, which is important in cell detoxification and converts hemithioacetals of methylglyoxal (a cytotoxic byproduct of sugar metabolism that may react with DNA or proteins and introduce nucleic acid strand breaks, elevated mutation frequencies and structural or functional changes of the proteins) and glutathione into Dlactate. GlxI accepts both the S and R enantiomers of hemithioacetal, but converts them to only the S-D enantiomer of lactoylglutathione. Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 68 publications
(233 reference statements)
5
7
0
Order By: Relevance
“…With more accurate hybrid quantum mechanics/molecular mechanics (QM/MM) calculations, we confirmed the higher basicity of Glu-172 and showed that Glu-172 is more flexible than Glu-99, not only in the protein but also during the proton exchange reaction of glutathiohydroxyacetone . In our fourth study, we returned to the normal single-substrate reaction of GlxI, scanning all possible proton transfers from the reactant states of S - and R - HTA to SLG with QM/MM calculations and a very large QM system . Our results confirmed a previously proposed reaction mechanism for the S substrate, shown in Scheme , and we proposed a new mechanism for the R substrate (cf.…”
Section: Introductionsupporting
confidence: 74%
See 4 more Smart Citations
“…With more accurate hybrid quantum mechanics/molecular mechanics (QM/MM) calculations, we confirmed the higher basicity of Glu-172 and showed that Glu-172 is more flexible than Glu-99, not only in the protein but also during the proton exchange reaction of glutathiohydroxyacetone . In our fourth study, we returned to the normal single-substrate reaction of GlxI, scanning all possible proton transfers from the reactant states of S - and R - HTA to SLG with QM/MM calculations and a very large QM system . Our results confirmed a previously proposed reaction mechanism for the S substrate, shown in Scheme , and we proposed a new mechanism for the R substrate (cf.…”
Section: Introductionsupporting
confidence: 74%
“…On the other hand, time-course experiments support the two-substrate mechanism for yeast GlxI . Nevertheless, most studies have concentrated on the single-substrate mechanism. , However, recently, Gonzales et al proposed the two-substrate mechanism shown in Scheme , based on a crystallographic study on Zm GlxI. They showed that Zm GlxI can bind intact H-SG in the active site and gives a tunnel with an independent binding site for MG.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations